Investigation of the protective role of fisetin against doxorubicin-induced liver injury in rats - Deniz, Ömür Gülsüm (The European Research Journal, 2025)
Objectives: The aim of the present research was to histopathologically investigate the potentially advantageous effects of the flavonoid fisetin on liver damage induced by the chemotherapeutic drug doxorubicin (DOX) in rats. Methods: Thirty-five Wistar albino female rats were randomized in five as Control, dimethyl sulfoxide (DMSO, solvent), fisetin (50 mg/kg/day; 7 days i.p.), DOX (single dose, 10 mg/kg; i.p.) and DOX+fisetin (10 mg/kg DOX+50 mg/kg/day fisetin for 7 days). Livers were harvested, fixed in 10% formalin, and processed for histopathology by hematoxylin-eosin staining. Central to these analyses of damage parameters for inflammation, sinusoidal dilatation, and hepatocyte injury were examined histopathologically. Results: The DOX group had severe hepatocyte degeneration, inflammation, and sinusoidal dilatation. In contrast, the DOX+fisetin group expressed mild sinusoidal dilatation and insignificant inflammatory change. In this context, statistical significance was found between the DOX group and the DOX+fisetin group in terms of hepatocyte degeneration and inflammation (P